Effect of Urea Molasses Mineral Block Supplementation on Milk Production in Murrah Buffalo under Small holder’s Production System - Bipate, Mahesh (Indian Journal of Animal Nutrition, 2021)
The present study was conducted at farmer’s field in Muzaffarnagar district of Uttar Pradesh to assess the response of urea molasses mineral block (UMMB) supplementation on milk production and body condition score in buffaloes. Twenty Murrah buffaloes in early lactation stage were selected and divided into two groups of 10 each. Animals of T1 group were given free access to urea molasses UMMB for two-three hours in the morning in addition to their normal ration for eight weeks after adaptation period of two weeks. However, the buffaloes in control (T0) group did not receive any supplement. The buffaloes were managed as per the standard feeding practices followed by the farmers. Significant increase in milk yield (P<0.05) was recorded due to feeding of UMMB as compared to control group. The daily milk yield of buffaloes was increased by 26.95 % due to supplementation of UMMB. Considering the present cost of feed supplement and the market price of milk, UMMB supplementation appears to be both economical and cost effective. Supplementation had a positive effect on milk production and BCS of buffaloes maintained under small holder conditions. However, there is need for long-term studies on more number of milch animals to assess the response of UMMB supplementation on animals’ health, production and reproductive performance under smallholder conditions.